2021
DOI: 10.1002/evl3.240
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal pleiotropy structures genetic covariance

Abstract: Quantitative genetic theory proposes that phenotypic evolution is shaped by G, the matrix of genetic variances and covariances among traits. In species with separate sexes, the evolution of sexual dimorphism is also shaped by B, the matrix of between‐sex genetic variances and covariances. Despite considerable focus on estimating these matrices, their underlying biological mechanisms are largely speculative. We experimentally tested the hypothesis that G and B are structured by hormonal pleiotropy, which occurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…The ontogenetic period over which sex-biased gene expression emerges in brown anoles implicates maturational effects of gonadal steroid hormones (e.g., androgens and estrogens), consistent with a large body of evidence linking androgens and estrogens to the development of sexual dimorphism in a variety of secondary sexual characteristics and across diverse vertebrate taxa (for reviews, see Roberts, Buchanan and Evans, 2004 ; Fusani, 2008 ; Jennings and de Lecea, 2020 ; Rey, 2021 ). In line with this view, previous work in brown anoles has shown that the steroid hormone testosterone induces the development of male-typical phenotypes (e.g., increased growth and body size, elevated metabolic rate, reduced fat storage, elaboration of the dewlap as a signaling ornament) in both males and females ( Cox et al, 2009a , 2015 , 2017 ; Wittman et al, 2021 ). Exogenous testosterone also masculinizes the liver transcriptome of juvenile females, particularly for growth-regulatory genes with naturally sex-biased expression, such as growth hormone receptor ( GHR ), insulin-like growth factors ( IGF1 , IGF2 ), and their receptors and binding proteins ( Cox et al, 2017 ).…”
Section: Introductionmentioning
confidence: 57%
“…The ontogenetic period over which sex-biased gene expression emerges in brown anoles implicates maturational effects of gonadal steroid hormones (e.g., androgens and estrogens), consistent with a large body of evidence linking androgens and estrogens to the development of sexual dimorphism in a variety of secondary sexual characteristics and across diverse vertebrate taxa (for reviews, see Roberts, Buchanan and Evans, 2004 ; Fusani, 2008 ; Jennings and de Lecea, 2020 ; Rey, 2021 ). In line with this view, previous work in brown anoles has shown that the steroid hormone testosterone induces the development of male-typical phenotypes (e.g., increased growth and body size, elevated metabolic rate, reduced fat storage, elaboration of the dewlap as a signaling ornament) in both males and females ( Cox et al, 2009a , 2015 , 2017 ; Wittman et al, 2021 ). Exogenous testosterone also masculinizes the liver transcriptome of juvenile females, particularly for growth-regulatory genes with naturally sex-biased expression, such as growth hormone receptor ( GHR ), insulin-like growth factors ( IGF1 , IGF2 ), and their receptors and binding proteins ( Cox et al, 2017 ).…”
Section: Introductionmentioning
confidence: 57%
“…Greater male-male competition is associated with greater SSD in lizards [75,76], but the effects of female-female competition have not been tested to our knowledge. By contrast, developmental integration between body and dewlap size has been shown in anoles [40,41]. Thus, for now, we interpret lower SSD to more likely reflect less male-male competition and call on future studies to examine the relationship between female-female competition and SSD.…”
Section: (C) the Pleiotropy Hypothesismentioning
confidence: 69%
“…We suggest a vital role for cis-regulatory elements, in particular AREs, in sexual selection as they can help resolve intralocus conflict by using sex-biased signals to create sex-biased gene expression that can lead to sexual dimorphism (Wittman et al, 2021, Cox et al, 2017. Importantly, there are multiple mechanisms for sex-biased expression (Mank, 2017, Ellegren and Parsch, 2007, Wright et al, 2018 and increasing genome-wide counts alone cannot explain the entirety of a genomic response to sexual selection.…”
Section: Discussionmentioning
confidence: 97%
“…There is evidence that sex-biased regulation via hormones or other signaling pathways can lead to sexbiased gene expression (Mank, 2017, Oliva et al, 2020, Anderson et al, 2020. Recent studies have suggested that sex-biased hormones have pleiotropic effects that reduce genetic correlations between the sexes (Wittman et al, 2021), and many genes have differential effects on the phenotype depending on the bearing sex (van der Bijl and Mank, 2021). Hence, genomic regions associated with sex-biased signaling could contribute to the phenotypic expression of traits under sexual selection and thus respond to sexual selection.…”
mentioning
confidence: 99%